Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ebiom.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-Specific Immunotherapy Targeting CD4-Positive T Cells in Celiac Disease: Safety, Pharmacokinetics, and Effects on Intestinal Histology and Plasma Cytokines with Escalating Dose Regimens of Nexvax2 in a Randomized, Double-Blind, Placebo-Controlled Phase 1 Study

Abstract: BackgroundNexvax2® is a novel, peptide-based, epitope-specific immunotherapy intended to be administered by regular injections at dose levels that increase the threshold for clinical reactivity to natural exposure to gluten and ultimately restore tolerance to gluten in patients with celiac disease. Celiac disease patients administered fixed intradermal doses of Nexvax2 become unresponsive to the HLA-DQ2·5-restricted gluten epitopes in Nexvax2, but gastrointestinal symptoms and cytokine release mimicking gluten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 29 publications
0
42
0
1
Order By: Relevance
“…Table shows the characteristics of the 93 patients who had pre‐treatment duodenal biopsies collected across three phase 1 trials and one phase 2 study investigating Nexvax2 in patients with coeliac disease. Disposition of patients in the phase 1 studies who had biopsies has been reported previously, and is shown in Figure for patients in the phase 2 study. Patient characteristics were similar for the four studies.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Table shows the characteristics of the 93 patients who had pre‐treatment duodenal biopsies collected across three phase 1 trials and one phase 2 study investigating Nexvax2 in patients with coeliac disease. Disposition of patients in the phase 1 studies who had biopsies has been reported previously, and is shown in Figure for patients in the phase 2 study. Patient characteristics were similar for the four studies.…”
Section: Resultsmentioning
confidence: 69%
“…Biopsy collection, processing and quantitative histology methods in the first and second phase 1 studies have been described in detail elsewhere . Briefly, biopsies were collected from four sites: the duodenal bulb, and from the first, second and third parts of the duodenum.…”
Section: Methodsmentioning
confidence: 99%
“…16 Using this approach, Nexvax2 was ultimately delivered at levels up to 900 µg, without dose-limiting side effects and well above the assessed maximum tolerated first dose (150 µg), which although tolerable, elicited dosedependent symptoms and a significant cytokine increase. 16 Using this approach, Nexvax2 was ultimately delivered at levels up to 900 µg, without dose-limiting side effects and well above the assessed maximum tolerated first dose (150 µg), which although tolerable, elicited dosedependent symptoms and a significant cytokine increase.…”
Section: Introductionmentioning
confidence: 99%
“…With evidence of rapid post-dose immune-system engagement, and the appearance of peak circulating peptide levels within an hour of intradermal administration, 13,16 we decided to explore the feasibility of subcutaneous injection. This report details the results of Phase-1 study to assess the clinical profile and general tolerability of a Nexvax2 subcutaneous dose-escalation regimen, and the respective pharmacokinetic and pharmacodynamic profiles of subsequent 900-µg doses of Nexvax2 administered via subcutaneous or intradermal injection to HLA-DQ2.5+ coeliac disease patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies demonstrated the safety of intradermal administration of Nexvax2 in patients with coeliac disease and, though not powered for efficacy, showed signals for improvement in symptoms and duodenal histology . Theoretically, intradermal administration exposes cutaneous antigen‐presenting cells to gliadin peptides, which may represent an important mechanism of action.…”
mentioning
confidence: 99%